Rheological and Nutritional Characterization of Sweet Corn By-Product (Cob) to Develop a Functional Ingredient Applied in Dressings - Castillo, Sandra; Rodríguez, Alexis; Bautista-Villarreal, Minerva; García-Solano, Nallely; Gallardo-Rivera, Claudia; Báez-González, Juan G.; Sánchez-García, Eduardo; García-Alanis, Karla G. (Frontiers in Nutrition, 2021)
In this study, a flour from corn cob (central core of the maize ear, stage R4) was obtained through three treatments. The three flours obtained were characterized by bromatological analysis, yield, and granulometry. Additional dressing-type oil in water (O/W) emulsions were developed, varying the formulation by incorporating distinct amounts of corn cob flour. The formulations' stability was evaluated during 21 days, determining the particle size, creaming index, coalescence rate, consistency coefficient (k), and flow behavior indices (n). Results have shown significant differences in protein, fat, and carbohydrates content in the flour depending on the cooking treatment. A good percentage of grinding yield was obtained (98%) and several fractions by granulometry (60, 120, 250 MESH), which presented differences in their nutritional content. Finally, the particle size of O/W emulsions developed varied among formulations. The combination of 0.6% of xanthan gum (XG) and corn cob flour presented major stability average droplet size. No significant differences were observed in the coalescence rate values for the three formulations. Still, significant differences in the creaming index were evidenced in those formulations without XG or corn cob flour. The results of consistency coefficient (k) and flow behavior indices (n) suggest a possible synergy between XG and flour of corn cob for enhancing the viscosity and pseudoplasticity of dressings in a concentration-dependent manner.